Breeding status of Red-billed Choughs Pyrrhocorax pyrrhocorax in the UK and Isle of Man in 2014. Issue 4 (2nd October 2018) - Hayhow, D. B.; Johnstone, I.; Moore, A. S.; Mucklow, C.; Stratford, A.; Šúr, M.; Eaton, M. A.
ABSTRACT: Capsule: In 2014 a survey of Red-billed Choughs Pyrrhocorax pyrrhocorax in the UK and Isle of Man found substantial variation in regional trends. The population has, however, remained stable overall since 2002, with a total of 433 breeding pairs recorded. Aims: The aim of the survey was to produce new estimates of the breeding populations and additional non-breeding birds for the Red-billed Chough in the UK and Isle of Man, and calculate national and regional population trends since previous surveys in 2002 and 1992. Methods: A complete census was attempted, using similar field methods to previous surveys. All known breeding sites and areas of adjacent suitable habitat within the range were surveyed between April and June 2014, with additional surveys on the Isle of Man in 2015. Evidence of breeding was established based on behaviours recorded during two standard visits. Results: The UK and Isle of Man population was estimated at 433 pairs, the majority found in Wales (55%) and Isle of Man (31%). Increases in the Isle of Man, Cornwall and south Wales contrasted with declines recorded in Scotland and in parts of north and mid-Wales. Trends differed regionally and between coastal and inland nesting areas. Conclusions: Numbers of Choughs in the UK and Isle of Man remained stable overall between 2002 and 2014, but trends varied between geographically distinct populations, suggesting the action of diverse drivers of change. Conservation efforts need to be responsive to these pressures by maintaining and enhancing habitat and food resources where required. Where populations are small, research needs to be targeted towards identifying critical demographic stages and facilitating gene flow among adjacent populations.